Cross country ski base tuning with structure imprint tools - Breitschädel, F.; Lund, O; Loset, S. (Procedia Engineering, 2010)
The importance of skis that have optimal glide in ski competitions is significant, since the margin between success and failure is often just seconds. The ski base structure is one of the most important factors that affects the glide. The structure can be divided into a permanent grind and a manual structure made by a hand tool. The use of structure hand tools has increased during recent years. This method allows the skier to continue to use the same skis from race to race but with the possibility of having a different ski base structure to suit the conditions. However, this approach depends on a good method for resetting the manual structure after the first race. Experiments were performed to investigate methods for resetting the structure made by hand tools. Currently, the most common method is to melt in glide wax. This was shown to be satisfactory but, as full resetting is not necessarily achieved after one treatment, the use of an incubator or a hot box would be preferential.